SPHDZ book #1! - Scieszka, Jon (Scieszka, Jon. SPHDZ, 2010)
On his first day at Brooklyn's P.S. 858, fifth-grader Michael K. is teamed with two very strange students, and while he gradually comes to believe they are aliens who need his help, he has trouble convincing anyone else of the truth.